Overview of Air-Rail Passenger Transport Relationship from 1997 to 2018 - Waralee Peetawan (My University, 2020)
World international passenger transport nowadays is dominated by air transport, while domestic passenger transport in certain region relies on rail transport. Aviation and railroad industry have been a rivalry since the introduction of commercial airlines. Although the relationships between both modes are initially competition, there are several other forms of relationship including cooperation and integration. This paper identified and categorized research themes for air-rail passenger transport relationship from research papers published between 1997 and 2018 by using content-based analysis. The literatures included in this paper focused on transportation science disciplines, namely economic, social, environment, and operations. Other analysis context are the analysis of word frequency and trend analysis for geographical area of research. Air-rail transport research themes were identified as modal comparison, modal influence, modal competition, modal cooperation, and modal integration. It has been found that in the early years, Europe is the region that dominate the research on air-rail passenger transport. However, China is an emerging country over the past five years. Additionally, research theme relies heavily on modal competition and modal influence.
Keywords: Rivalry; Passenger transport; Aviation Industry Analysis and Trends